Synthesis of diazabicyclo compounds possessing an α-nitrolactam framework. Issue 19 (6th May 2015) - Asahara, Haruyasu; Takeda, Shota; Saigo, Kazuhiko; Nishiwaki, Nagatoshi
Graphical abstract: Abstract: Diazabicyclo compounds possessing an α-nitrolactam framework were directly synthesized upon treatment of α-nitro-δ-keto esters with diamines. This reaction proceeds via pseudo-intramolecular process. In this process, the formation of ammonium nitronate is a key step, by which the amino group and the ketone carbonyl group are in close proximity to cause the imine formation efficiently. The following tandem bicyclization constructs 1, 7-diaza-3-nitro-2-oxobicyclic systems having two aryl groups at the 4- and 6-positions.